Seedbank persistence and emergence pattern of Argemone mexicana, Rapistrum rugosum and Sonchus oleraceus in the eastern grain region of Australia - Sudheesh Manalil (Nature Portfolio, 2021)
Abstract A thorough understanding of the emergence pattern and persistence of weed seeds is a prerequisite in framing appropriate weed management options for noxious weeds. In a study conducted at the University of Queensland, Australia, the emergence and seed persistence behavior of three major weeds Sonchus oleraceous, Rapistrum rugosum, and Argemone mexicana were explored with seeds collected from Gatton and St George, Queensland, Australia, with an average annual rainfall of 760 and 470 mm, respectively. Seed persistence was evaluated by placing seeds at the surface layer (0 cm) or buried at 2 and 10 cm depths enclosed in nylon mesh bags and examined their viability for 42 months. In another study, the emergence pattern of four populations, each from these two locations, was evaluated under a rainfed environment in trays. In the mesh-bag study, rapid depletion of seed viability of S. oleraceous from the surface layer (within 18 months) and lack of seed persistence beyond two years from 2 and 10 cm depths were observed. In trays, S. oleraceous germinated 3 months after seeding in response to summer rains and there was progressive germination throughout the winter season reaching cumulative germination ranging from 22 to 29% for all the populations. In the mesh-bag study, it took about 30 months for the viability of seeds of R. rugosum to deplete at the surface layer and a proportion of seeds (5 to 13%) remained viable at 2 and 10 cm depths even at 42 months. Although fresh seeds of R. rugosum exhibit dormancy imposed due to the hard seed coat, a proportion of seeds germinated during the summer months in response to summer rains. Rapid loss of seed viability was observed for A. mexicana from the surface layer; however, more than 30% of the seeds were persistent at 2 and 10 cm depths at 42 months. Notably, poor emergence was observed for A. mexicana in trays and that was mostly confined to the winter season.